Collaborative Model for Using Village Funds to Support Maternal and Child Health Resilience in Cirebon Regency - Jati, Sutopo Patria; Budiyanti, Rani Tiyas; Nandini, Nurhasmadiar; Yunita Dewanti, Nikie Astorina; Kusariana, Nissa (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
COVID-19 disease has the potency to increase maternal and child mortality rates. It is because pregnant women and children include the vulnerable groups. To increase maternal and child health resilience during the COVID-19 pandemic, community empowerment was needed. Many programs can be done through innovative planning and budgeting. The village fund can be an alternative solution in this condition. This research was qualitative research that used Focus Group Discussion with the participant contains village head, cadres, health professional, Department of Health agent, Village Community Empowerment Service, Regional Planning and Development Agency in the Cirebon Regency.  Based on the research, maternal and child health resilience could be improved through developing the innovation program related to maternal and child health such as support in COVID-19 vaccination to pregnant women, support to high-risk pregnant women, and so on. The collaborative model could be done between village funding, Corporate Social Responsibility (CSR), Family Welfare Empowerment’s funding, and non-governmental funding.  To identify the situation analysis it can be done through discussion at the village level (Musdes). It also can collaborate the maternal and child program with the national program, adaptation of new habits, and strategic local issues.Abstrak: Penyakit COVID-19 berpotensi meningkatkan angka kematian ibu dan anak. Sebab, ibu hamil dan anak-anak termasuk kelompok rentan. Untuk meningkatkan ketahanan kesehatan ibu dan anak di masa pandemi COVID-19, diperlukan pemberdayaan masyarakat. Banyak program yang dapat dilakukan melalui perencanaan dan penganggaran yang inovatif. Dana desa bisa menjadi alternatif solusi dalam kondisi ini. Penelitian ini merupakan penelitian kualitatif dengan metode Focus Group Discussion dengan peserta terdiri dari kepala desa, kader, tenaga kesehatan, Dinas Kesehatan, Dinas Pemberdayaan Masyarakat Desa, Pemberdayaan Kesejahteraan Keluarga (PKK), dan Badan Perencanaan dan Pembangunan Daerah di Kabupaten Cirebon. Berdasarkan penelitian, ketahanan kesehatan ibu dan anak dapat ditingkatkan melalui pengembangan program inovasi terkait kesehatan ibu dan anak seperti dukungan vaksinasi COVID-19 pada ibu hamil, dukungan pada ibu hamil risiko tinggi, dan sebagainya. Model kolaboratif dapat dilakukan dengan dukungan dana desa, Corporate Social Responsibility (CSR), pendanaan PKK, dan swadaya masyarakat. Untuk mengetahui kebutuhan serta analisis situasi, diskusi dapat dilakukan melalui musyawarah tingkat desa (Musdes). Kolaborasi program dan pendanaan juga dapat dilakukan dengan menginsersikan program kesehatan ibu dan anak dengan program strategis nasional, adaptasi kebiasaan baru, dan program strategis terkait isu lokal.